Influence of Social Support, Financial Status, and Lifestyle on the Disparity Between Inflammation and Disability in Rheumatoid Arthritis. Issue 5 (28th December 2022) - Gwinnutt, James M.; Norton, Sam; Hyrich, Kimme L.; Lunt, Mark; Combe, Bernard; Rincheval, Nathalie; Ruyssen‐Witrand, Adeline; Fautrel, Bruno; McWilliams, Daniel F.; Walsh, David A.; Nikiphorou, Elena; Kiely, Patrick D. W.; et al.
Abstract : Objective: To investigate how social support, financial status, and lifestyle influence the development of excess disability in rheumatoid arthritis (RA). Methods: Data were obtained from the Étude et Suivi des Polyarthrites Indifférenciées Récentes (ESPOIR) cohort study of people with RA. A previous analysis identified groups with similar inflammation trajectories but markedly different disability over 10 years; those in the higher disability trajectory groups were defined as having "excess disability." Self‐reported data regarding contextual factors (social support, financial situation, lifestyle) were obtained from participants, and they completed patient‐reported outcome measures (pain, fatigue, anxiety, depression) at baseline. The direct effect of the contextual factors on excess disability and the effect mediated by patient‐reported outcome measures were assessed using structural equation models. Findings were validated in 2 independent data sets (Norfolk Arthritis Register [NOAR], Early Rheumatoid Arthritis Network [ERAN]). Results: Of 538 included ESPOIR participants (mean age ± SD 48.3 ± 12.2 years; 79.2% women), 200 participants (37.2%) were in the excess disability group. Less social support (β = 0.17 [95% confidence interval (95% CI) 0.08, 0.26]), worse financial situation (β = 0.24 [95% CI 0.14, 0.34]), less exercise (β = 0.17 [95% CI 0.09–0.25]), and less education (β = 0.15 [95% CI 0.06, 0.23]) were associated with excess disability group membership; smoking, alcohol consumption, and body mass index were not. Fatigue and depression mediated a small proportion of these effects. Similar results were seen in NOAR and ERAN. Conclusion: Greater emphasis is needed on the economic and social contexts of individuals with RA at presentation; these factors might influence disability over the following decade.